RNA Chaperones Hfq and ProQ Play a Key Role in the Virulence of the Plant Pathogenic Bacterium Dickeya dadantii - Leonard, Simon; Villard, Camille; Nasser, William; Reverchon, Sylvie; Hommais, Florence (Frontiers in Microbiology, 2021)
Dickeya dadantii is an important pathogenic bacterium that infects a number of crops including potato and chicory. While extensive works have been carried out on the control of the transcription of its genes encoding the main virulence functions, little information is available on the post-transcriptional regulation of these functions. We investigated the involvement of the RNA chaperones Hfq and ProQ in the production of the main D. dadantii virulence functions. Phenotypic assays on the hfq and proQ mutants showed that inactivation of hfq resulted in a growth defect, a modified capacity for biofilm formation and strongly reduced motility, and in the production of degradative extracellular enzymes (proteases, cellulase and pectate lyases). Accordingly, the hfq mutant failed to cause soft rot on chicory leaves. The proQ mutant had reduced resistance to osmotic stress, reduced extracellular pectate lyase activity compared to the wild-type strain, and reduced virulence on chicory leaves. Most of the phenotypes of the hfq and proQ mutants were related to the low amounts of mRNA of the corresponding virulence factors. Complementation of the double mutant hfq-proQ by each individual protein and cross-complementation of each chaperone suggested that they might exert their effects via partially overlapping but different sets of targets. Overall, it clearly appeared that the two Hfq and ProQ RNA chaperones are important regulators of pathogenicity in D. dadantii. This underscores that virulence genes are regulated post transcriptionally by non-coding RNAs.